Modelling and Optimization Approach of Quantitative Environmental Ergonomics in Malaysian Automotive Industry - Isa, Halim (National Institute of Occupational Safety and Health, 2012)
Environmental factors such as temperature, lighting and noise have very significant impact to workers' health, safety, comfort, performance and productivity. In an ergonomically design industrial work environment, these factors need to be controlled at their optimum levels. The main objective of this study is to find the effect of temperature, illuminance and sound pressure level on workers' productivity in an automotive industry. To perform this study, a workstation in an automotive component manufacturing was selected as the location of the study. Results of data analysis showed there were relationships between temperature, illuminance and noise on workers' productivity. Later, the authors have developed multiple linear equation models to represent the relationship betweeen temperature, illuminance and noise on the workers' productivity. These multiple linear equation models could be used to predict the production rate for the worksation by referring to the value of temperature, illuminance and noise level.